A New Approach to the Psychological Identification of Mazu Costume Culture - liu, lixia; Su, Hao; San Juan, Felisse Marianne Z. (Pacific International Journal, 2024)
This research delves into the profound significance of Mazu costume culture, a distinctive cultural emblem and societal standard that instigates emotional bonds and fosters a sense of belonging within the Mazu faith community. Utilizing innovative methodologies, we probe into the psychological identification linked to Mazu costume culture. Eye-tracking technology, electroencephalogram (EEG), virtual reality, and social media analysis are harnessed to gauge the emotional dispositions and levels of identification individuals associate with Mazu costumes. The novelty of this paper lies in its methodological approach, intertwining theories and methodologies from psychology, cultural studies, and computational science to provide a comprehensive, multi-faceted investigation into the psychological identification of Mazu costume culture.